Technological, Organizational, and Environmental Determinants of Digital Platform Adoption by SMEs - Muhammad Awaluddin (Indonesian Journal of Research and Service Studies, 2024)
This study investigates the determinants of digital platform adoption among small and medium enterprises (SMEs) by employing the Technology–Organization–Environment (TOE) framework. The model examines three independent factors—technological, organizational, and environmental—influencing the dependent variable, namely digital platform adoption. Data were collected from 300 SMEs through a structured questionnaire using a four-point Likert scale. The analysis employed Exploratory Factor Analysis (EFA) to validate construct dimensionality, followed by reliability testing using Cronbach’s Alpha, and hypothesis testing (H1–H6) to assess the relationships within the TOE framework.The results show that the Kaiser-Meyer-Olkin (KMO) value is 0.78 and Bartlett’s test is significant (χ² = 856.3, df = 136, p < 0.001), confirming the suitability of the data for factor analysis. EFA extracted three components aligned with the TOE framework, explaining 85% of the total variance. Communalities range between 0.68 and 0.84, indicating that the variables are well explained by the extracted factors. Reliability analysis demonstrates strong internal consistency, with Cronbach’s Alpha values of 0.884 for technological factors, 0.902 for organizational factors, and 0.861 for environmental factors. Corrected item-total correlations exceed 0.67, confirming the validity of each measurement item. Hypothesis testing (H1–H6) further reveals that technological readiness, organizational capabilities, and environmental pressures significantly influence digital platform adoption among SMEs, with technology emerging as the strongest determinant.These findings highlight the importance of strengthening digital infrastructure, leadership commitment, resource allocation, and government support to accelerate SME digital transformation. This study contributes both theoretically, by validating the TOE framework in the SME context, and practically, by offering actionable recommendations for managers and policymakers to foster sustainable digital adoption.